Risk Analysis Using Value at Risk Method on Bitcoin and JKSE Period 2017-2019 - Risty Mega Pramadita; Nora Amelda Rizal (Almana : Jurnal Manajemen dan Bisnis, 2020)
This research is motivated by Bitcoin that tends to be used as an alternative investment tool, and stock which is one of the most popular investment tools in the investment world. Both of these investments have characteristics of high fluctuating price movements. Thus, this study agrees to examine how much risk is faced by investors when choosing to invest in Bitcoin and Jakarta Composite Index (JKSE), using the Value at Risk (VaR) method. This research is using VaR calculation to estimates losses on an asset with a certain level of confidence and in a certain period and involves the GARCH model to estimate volatility. This research is used secondary data consisting of daily price data of Bitcoin obtained from coingecko.com and JKSE obtained from finance.yahoo.com. The research period is from January 1, 2017, to December 31, 2019. The results showed that Bitcoin has a higher risk compared to JKSE, which is about five times higher.